Análise comparativa das simulações computacionais e medições em campo dos critérios de desempenho acústico em vedações verticais internas e vedações horizontais. - Rezende, Emanuela Carvalho Lobo (2019)
In urban areas and large cities, numerous pollution problems have negative impacts on the environment and human health. Noise pollution is one of the problems that are potentially being treated by society due to the impact caused both in terms of comfort and the health hazards they cause. To promote better use and occupation of housing buildings, the acoustic quality of the environments has been sought through modifications to consolidated building systems and improvements in building technology. In this context, the NBR 15575, named as the performance standard, emerges, linking the performance of housing buildings to the aspects of comfort, safety and durability. The standard presents criteria to be met and the manner in which such parameters should be measured. Since acoustic performance is one of the requirements of the standard, the aim is to attenuate sound between environments, whose objective has involved not only builders, but also designers, material suppliers and users. Acoustic forecasting models from computational simulation (SC) has been the tool used to evaluate the acoustic behavior of the property, even before the work is done, thus enabling the reduction of post-adaptation costs. This research aims to evaluate the reliability of computational simulation by analyzing data from simulations and field measurements (MC) of 14 case studies, in relation to internal vertical sealing systems (SVVI) and horizontal sealing systems (SVH). Comparative analysis of 75 SVVI SC and MC data showed that more than 50% of the simulation data showed values compatible with the field measurement, in the sense that they were considered potentially equal, taking into account the uncertainty of the predicted field measurement in the evaluation methodology contained in the standard, in the order of ±2dB. Removing discrepant data, due to the limitations of the program, this percentage reaches 69%. For the 228 SVH data, of which 116 were for SVH-RA and 102 for SVH-RI, the comparative study showed a 38% acceptability between SVH-RA measurement and simulation and 46% for SVH-RI. This acceptability refers to the values within the ±2dB range of the afore mentioned uncertainty. The data also showed variation between SC and MC, sometimes presenting a larger SC, sometimes a larger MC. The expectation was that the results would converge, but where situations of MC values greater than SC occurred, it is concluded that the field will enjoy better performance than the minimum of the projected standard. The contrary confirmed that unforeseen factors in the field, construction failures, seals etc. compromise the expected performance. It was also verified, through variation of the input data, that the fidelity to the technical specification of the projected systems reproduces reliable values, and the opposite results in the fragility and discrepancy of the data. In general, the results of the comparative analysis point out as positive the use of computer simulation, since part of the percentage out of the acceptability in this study represents uncertainty in the measurements, being, therefore, the simulation an effective instrument of forecast and useful in the search for acoustic quality residential buildings.